Binding of Aggregated Immunoglobulins to the Human Platelet Fc Receptors: A Mechanism of Platelet to Platelet Bridging - Parbtani, Anwar; Clark, William F; Caveney, Anita; Reid, Bruce (Thrombosis and Haemostasis, 1987)
Aggregated immunoglobulins react with human platelets by occupying the Fc receptors present on their surface, inducing aggregation and the release reaction. We studied the effect of heat aggregated gammaglobulins (HAGG) on ADP-induced aggregation of platelets. We used the minimum concentration of ADP required to induce a reversible aggregation of platelets without any substantial amount of serotonin (14C 5HT) release. EDTA (5 mM) added at the peak of platelet aggregation resulted in rapid deaggrcgation ot these platelets. However, incubation of platelets with HAGG at a dose that did not by itself induce any aggregation or release reaction, followed by ADP addition resulted in an irreversible platelet aggregation of greater magnitude accompanied by a substantial release of 14C-5HT. The addition of EDTA at the peak of platelet aggregation failed to deaggregate these platelets. To determine whether the augmented aggregation response and the inhibition of deaggiega-tion was due to HAGG or a consequence of platelet release products, we used thrombin-degranulated platelets. The augmented aggregation response and the inhibition of deaggregation due to HAGG and ADP could be demonstrated using these platelets. To confirm that the binding of HAGG to the platelet Pc receptors was responsible for these observations, we incubated platelets with an excess of Fc fragments of IgG prior to the addition of HAGG and ADP. This abolished the aggregation response observed previously. From this study we conclude that interplatelet bridging by HAGG renders the platelets hyperag-gregable and appears to be a mechanism involved in maintaining platelet aggregates.
Keywords: Platelet release reaction; Deaggregation; Immunoglobulins; Fc receptors